FUNCTIONING OF COMMUNITY HEALTH WORKERS IN THE FAMILY HEALTH STRATEGY - Elaine Regina Prudencio Silva; Luiza Helena Oliveira Cazola; Maria de Fátima Meinberg Cheade; Renata Palópoli Pícoli (Universidade Federal do Paraná, 2012)
This study aimed to characterize the functioning of the Community Health Workers in Family Primary Care Centers in Três Lagoas, in Mato Grosso do Sul. It is a descriptive study with a quantitative approach undertaken with 68 workers from seven Family Health Strategy Centers. The responses in the individual interviews were analyzed by descriptive statistics. The majority were women, aged between 40 and 49, married, who had completed middle school and had been working in that role for five to ten years. The majority had participated in the introductory course and all had undertaken some training. The participants reported knowing their responsibilities and indicated the home visit as the most frequent activity, and considered that actions for the control and prevention of dengue are inherent to their work; and they revealed that they undertake activities which are not their responsibility. It is concluded that community workers have weaknesses in recognizing their responsibilities in the performance of their activities.